Sonographic Lower Uterine Segment Thickness Measurement And Risk Of Uterine Scar Defect In Women With Previous Caesarean Section. - Habiba Sharaf Ali; Dr Shahina Ishtiq; Bina Fawad; Rabel Gul (ziauddin University, 2024)
Background: Risk of scar defect is inversely correlated with lower uterine segment thickness. The study aims to assess the diagnostic accuracy of sonographic measurement of the lower uterine segment thickness near term in predicting uterine scar defect in women with prior Caesarean section and ascertain the best cut-off value for predicting uterine rupture in our country. Methods: This observational case series study was carried out at Department of Gynecology and Obstetrics, Ziauddin University and Hospitals from January 2015 to June 2015. Women carrying singlet on pregnancy of 36-38 weeks with history of previous C-section were included in the study. Lower uterine segment measurement was done by transabdominal ultrasound at 36-38 weeks gestation and these women are followed up to the time of delivery. Results: A total of 180 patients based on inclusion criteria were recruited in the study. Significant association (p=.001) was found between LUS thickness values measured during pregnancy and status of scar at the time of delivery. No significant association was found between scar thickness and mode of delivery (p= .390). Scar dehiscence was noted in only one study participant. Conclusion: We support the proposition that antenatal measurement of lower uterine segment measurement in women with previous caesarean section is a reliable tool in deciding which women should be given a trial of labor. Key Words: Previous Caesarean Section, Lower Uterine Segment (LUS), Ultrasound Measurement, Pakistan